4000 years of environmental and climate change at Eilandvlei : a palynological investigation into the late Holocene palaeoenvironment of the Wilderness Embayment - Du Plessis, Nadia (Department of Environmental and Geographical Science, 2015)
It is a well-known fact that the South African palaeoenvironmental record is fairly limited, mainly because the environmental conditions here do not lend themselves to the preservation of proxy data sources. This being said, new evidence is emerging from the Wilderness Embayment along the Southern Cape coast of South Africa. This area is of particular interest from a palaeoclimate perspective due to its location within the small year round rainfall zone of South Africa, while the presence of both Fynbos and Afrotemperate forest within this region further highlights the importance of studies in the area. This study presents a new high resolution late Holocene pollen and charcoal record from Eilandvlei, extending from c. 3 800 cal yr BP to present. The record is marked by several significant periods -- largely corresponding to the timing of the three events that typify the late Holocene: the Neoglacial, the Medieval Climate Anomaly and the Little Ice Age. The record also encompasses the arrival of European colonists in the region ca. 1800 AD, marked by the appearance of Pinus, with subsequent notable fluctuations in other taxa, e.g. Podocarpus and Stoebe-type, possibly the expression of the anthropogenic effect on the landscape. This high resolution record thus highlights significant, albeit short term, fluctuations in climate and vegetation patterns along the Southern coast of South Africa and adds to the inadequate records available for the region thus far.